Age-dependent changes on fractalkine forms and their contribution to neurodegenerative diseases - Eugenín, Jaime; Eugenín-von Bernhardi, Laura; von Bernhardi, Rommy (Frontiers in Molecular Neuroscience, 2023)
The chemokine fractalkine (FKN, CX3CL1), a member of the CX3C subfamily, contributes to neuron-glia interaction and the regulation of microglial cell activation. Fractalkine is expressed by neurons as a membrane-bound protein (mCX3CL1) that can be cleaved by extracellular proteases generating several sCX3CL1 forms. sCX3CL1, containing the chemokine domain, and mCX3CL1 have high affinity by their unique receptor (CX3CR1) which, physiologically, is only found in microglia, a resident immune cell of the CNS. The activation of CX3CR1contributes to survival and maturation of the neural network during development, glutamatergic synaptic transmission, synaptic plasticity, cognition, neuropathic pain, and inflammatory regulation in the adult brain. Indeed, the various CX3CL1 forms appear in some cases to serve an anti-inflammatory role of microglia, whereas in others, they have a pro-inflammatory role, aggravating neurological disorders. In the last decade, evidence points to the fact that sCX3CL1 and mCX3CL1 exhibit selective and differential effects on their targets. Thus, the balance in their level and activity will impact on neuron-microglia interaction. This review is focused on the description of factors determining the emergence of distinct fractalkine forms, their age-dependent changes, and how they contribute to neuroinflammation and neurodegenerative diseases. Changes in the balance among various fractalkine forms may be one of the mechanisms on which converge aging, chronic CNS inflammation, and neurodegeneration.